Nutrition Factors in Breeding Place Media and Larva Density of Aedes Aegypti - Isye Dianti; Budiyono Budiyono; Tri Joko (Journal of Public Health for Tropical and Coastal Region, 2019)
Background: One of the stages of development to the growth of the Aedes aegypti is larvae stage. The larvae need nutrients to grow. A one of medium for breeding larvae is water in the container. Some of the important nutrients for growth are nitrate, phosphate, ammonia. This study aimed to analyze the relationship between nutrient levels in the water of the container density of Aedes aegypti larvae. Methods: Observational study with a cross-sectional with 119 houses as samples. Results:Test the relationship of nutritional factors with the density of Aedes aegypti larvae using the Pearson correlation test. The average distribution of nitrate was 0.787 mg / l, phosphate was 0.186 mg / l while ammonia was 0.603 mg / l and larval density was 66 tails. The study found that there was a correlation between the levels of nitrate, phosphate, ammonia and the density of Aedes aegypti larvae (p = 0.055 r = 0.022; p = 0.001, r = 0,929; p = 0.92, r = 0.975). Conclusion:The conclusions of this study were given the biggest contribution to the growth of Aedes aegypti larvae. A cooperative effort is needed to eliminate Aedes aegypti larvae.